FRAKSI AIR EKSTRAK DAUN WUNGU (Graptopphyllumpictum L.) SEBAGAI ANTIINFLAMASI TERHADAP TIKUS PUTIH JANTAN - Ramadhan Triyandi; Akhmad Rokiban; Catur Setia Pratiwi MS (Fakultas MIPA Universitas Tulang Bawang Lampung, 2020)
Abstract This study aims to determine the anti-inflammatory effect of the water extract of Daun wungu (Graptophyllum pictum L.) extract which was observed from the decrease in the volume of edema of rat’s feet which was induced by 1 % carrageenan as much as 0,1 ml, was carried out in 25 male white rats divided into 5 groups. Negative controlwas given distilled water given 5 % Na CMC, diclofenac sodium as a positive control with a dose of 0,9 mg/200 g BB and water fraction of wungu leaf extract with a dose 1 (1,125 mg/kg bb), dose 2 (2,25 mg/kg bb) dan dose 3 (4,5 mg/kg bb). The measurement of edema volume is carried out every hour for six hours after induced carrageenan. From the results of testing the water fraction of wungu leaf extract, % inhibition showed that the dose group 3 (4,5 mg/kg bb) had anti-inflammatory activity that was comparable to the positive control group. Of all dosage variatons in this study the effective dose which has the highest percentage of edema is the dose 3 (4,5 mg/kg bb). Based on the results of statistical analysis, the percentage of edema inhibition data on the water fraction of wungu lear extract from all dose variations showed significant differences with negative controls. Keyword : Graptophyllum pictum L Anti-Inflamasi